2016
DOI: 10.9790/0853-1507114853
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diabetic Retinopathy in Type II Diabetes Mellitus with Hba1c Levels: A Study

Abstract: :Purpose :To assess the association of Diabetic Rtinopathy in Type -II Diabetes Mellitus with HbA1c

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Rajendra Prasad et al observed in their study that there was an increase in the severity of retinopathy with higher levels of HbA1c. 9 Our study also showed similar results and we could also specifically postulate the correlation with vision-threatening diabetic retinopathy with HbA1c levels.…”
Section: Discussionsupporting
confidence: 85%
“…Rajendra Prasad et al observed in their study that there was an increase in the severity of retinopathy with higher levels of HbA1c. 9 Our study also showed similar results and we could also specifically postulate the correlation with vision-threatening diabetic retinopathy with HbA1c levels.…”
Section: Discussionsupporting
confidence: 85%
“…Prasad et al reported mean HbA1c levels of 9.25 + 1.59 and revealed an increasing trend in the severity of retinopathy with a rise in HbA1c levels. 16 A similar study was carried out in Saudi Arabia and it concluded that patients who had uncontrolled diabetes (high HbA1c levels) had 66.61% chance of developing diabetic retinopathy. 17 Relationship between diabetic retinopathy and HbA1c levels showed that severity of retinopathy increased as HbA1c levels were raised and this is also supported by many other similar studies.…”
Section: Discussionmentioning
confidence: 85%
“…Other study in Dhaka, Bangladesh-India on 80 type 2 DM patients also showed a positive correlation between RDW and HbA1c levels (r=0.45; p=0.001) (Jahan et al, 2018). Another study that compared the correlation of RDW and HbA1c levels in male (r= 0.40) and female (r= 0.04) (Jahan et al, 2018).…”
mentioning
confidence: 88%
“…RDW and HbA1c which have a positive relationship are mentioned in various studies on DM and are considered to have a role in the course of the disease and its complications. Routinely measuring RDW values can be used as a practical biomarker in assessing risk in DM patients (Jahan et al, 2018) A study in Pakistan on 119 type 2 DM patients found a positive and significant correlation berween HbA1c and RDW (r= 0.193; p= 0.035), while other hematological parameters, such as MCV, hemoglobin and platelets were not correlated with RDW (Bhutto, Abbasi and Abro, 2019).…”
mentioning
confidence: 99%